2005
DOI: 10.1159/000086863
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal Thyroid Hormone Supplementation Rescues Developmental Abnormalities Induced by Congenital-Neonatal Hypothyroidism in the Rat Retina

Abstract: Thyroid hormones (TH) play a key role in central nervous system development. We have studied the influence of congenital and neonatal hypothyroidism on retinal development and the effects of postnatal TH supplementation. An experimental model was set up using Wistar rats by inducing chemical thyroidectomy during gestation and suckling. Eyes from control (CG) and TH-depleted (THDG) groups of animals were obtained at postnatal days 10 and 25. In the THDG, there was a significant reduction in the retinal thicknes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 69 publications
(58 reference statements)
2
16
0
2
Order By: Relevance
“…Studies in rats have shown that pharmacologically induced hypothyroidism during the gestation and suckling period results in reduced eye size, delayed retinal development and morphological abnormalities in photoreceptors as well as in the inner retina, including reduced cell densities in the INL and GCL [11–14]. The time window for these wide-ranging effects of hypothyroidism can be narrowed down to the prenatal period.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in rats have shown that pharmacologically induced hypothyroidism during the gestation and suckling period results in reduced eye size, delayed retinal development and morphological abnormalities in photoreceptors as well as in the inner retina, including reduced cell densities in the INL and GCL [11–14]. The time window for these wide-ranging effects of hypothyroidism can be narrowed down to the prenatal period.…”
Section: Discussionmentioning
confidence: 99%
“…Prenatally, TH is an important regulator in the normal development of the eye and retina [11–14]. Postnatally, TH is crucial for the differentiation of spectral cone types.…”
Section: Introductionmentioning
confidence: 99%
“…, 2007). Chemically induced congenital and neonatal hypothyroidism significantly reduces thickness, layering, volume, cell number and nuclear volumes in the retinas of Wistar rats (Pinazo‐Duran et al. , 2005).…”
Section: Discussionmentioning
confidence: 99%
“…It regulates intrinsic mechanisms for controlling retinal cytoarchitecture and layering [10]. As Gamborino et al [11] demonstrated in a rat model, the photoreceptor and ganglion cell layer thickness displayed significantly lower values in congenital-neonatal hypothyroidism.…”
Section: Discussionmentioning
confidence: 99%